A theory for ranking distribution functions - Rolf Aaberge; Tarjei Havnes; Magne Mogstad (University of Oslo, Department of Economics, 2014)
We propose a general framework to unambiguously compare distributions functions in an economically interpretable way. Our framework provides complete ranking of any set of distributions and money metric interpretation of the social welfare level of a dominating distribution as compared to a dominated distribution. We show the usefulness of our framework using two empirical applications; the first assesses the welfare implications of changes in household income distributions over the business cycle, while the second performs a social welfare comparison of the actual and counterfactual outcome distributions from a policy experiment.
Keywords: D30; D63; I31; 330; distribution functions; stochastic dominance; social welfare; inequality